DIPLOMASI BENCANA: SEBUAH KATALIS PEMBANGUNAN KERJASAMA DAN PERDAMAIAN PASCA BENCANA TSUNAMI ACEH TAHUN 2004 [DISASTER DIPLOMACY: A CATALYST FOR POST-ACEH TSUNAMI DISASTER COOPERATION AND PEACE BUILDING IN 2004] - Ramadhani, Rizqisani; Rahmat, Hayatul Khairul; Banjarnahor, Joshua (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2024)
Natural disasters require international attention because of their widespread impacts, including suffering, damage, and destruction of infrastructure. The 2004 Aceh earthquake and tsunami devastated much of Indonesia and killed an estimated 237,448 people. The Free Aceh Movement (GAM) rebellion began in 1976. After the tsunami, a peace agreement was reached in eight months, but political and internal factors were more influential in the long-term peace. This study uses a library research method. Library research is a method of collecting data by reviewing books, literature, records, and various reports that are relevant to the problem to be solved. A disaster is an event that threatens life and livelihoods, caused by natural, non-natural, or human causes. Its impacts are broad, from loss of life to environmental damage. Disaster diplomacy is an effort to use disaster-related activities to promote cooperation between countries or reduce conflict. An example is the case of Aceh, where the tsunami became a catalyst for peace between the Indonesian government and GAM. Both disasters and disaster diplomacy have significant impacts on society and international relations. Disasters have complex physical and socio-economic impacts. Disaster diplomacy shows that although devastating, disasters can also be catalysts for cooperation and peace, such as the peace in Aceh after the 2004 tsunami. Disaster management must include technical responses, risk mitigation, strengthening health systems, and international diplomacy to reduce impacts and strengthen global cooperation.